Menilik Balik Inflasi : Pemikiran Ekonomi Islam Al Maqrizi - Anggraini, Misi; Azis, Saipul; Srilupita, Alda; Hulwati, Hulwati (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2023)
Inflation is an economic condition that countries around the world cannot avoid. Including from developing countries to developed countries. Many economists discuss the problem of inflation in their economic thinking. One of the famous Islamic economists with his theory of inflation is Al-Maqrizi, namely Taqiyuddin Abu Al-Abbas Ahmad bin Ali bin Abdul Qadir Al-Husaini. This figure said that the cause of inflation was natural inflation, namely inflation that had an impact on natural influences such as natural disasters. Thus, natural disasters are outbreaks of the Covid-19 virus and economic transactions are blocked in all sectors, even the economy. This is not going as smoothly as usual Conditions that have an impact on increasing the prices of many other goods and services. This resulted in food shortages, various diseases and death among the people. Human error inflation, namely inflation caused by human error, in this article only focuses on post-pandemic inflation. This causes economic paralysis in various countries around the world and inflation, which can even turn into deflation. But this time the focus is on the post-Covid-19 pandemic, especially in Indonesia.